Assessing the macroeconomic impact of bank intermediation shocks: A structural approach - Kaiji Chen; Tao Zha (Federal Reserve Bank of Atlanta, 2015)
We take a structural approach to assessing the empirical importance of shocks to the supply of bank-intermediated credit in affecting macroeconomic fluctuations. First, we develop a theoretical model to show how credit supply shocks can be transmitted into disruptions in the production economy. Second, we use the unique micro-banking data to identify and support the model's key mechanism. Third, we find that the output effect of credit supply shocks is not only economically and statistically significant but also consistent with the vector autogression evidence. Our mode estimation indicates that a negative one-standard-deviation shock to credit supply generates a loss of output by 1 percent.
Keywords: E32; E44; G21; C51; C81; C82; 330; intermediation cost; credit supply channel; micro bank-level data; call report; senior loan officers; identification; supply and demand; intermediation costs; endogenous monitoring activities